Determinants Of Self-Confidence Of Buleleng Swimming Athletes - I Dewa Gede Bagus Adityarama Gunawan; Wasti Danardani; Ketut Chandra Adinata Kusuma; Syarif Hidayat (Universitas Sriwijaya, 2023)
Abstract The level of self-confidence becomes a foundation in a person when the athlete doing something, including swimming athletes.Â This study aims to determine the level of self-confidence of swimming athletes in the Buleleng contingent who will go down at the 2022 Pekan Olahraga Provinsi (Porprov). This quantitative descriptive study surveyed the level of self-confidence through questionnaires. The data is processed using the Validity and Reliability Test. The subject of this study was Buleleng swimming athletes. The samples were taken using purposive sampling techniques so that a total of 18 athletes were obtained. The result of this study is that there are 3 determining conditions in internal factors that will affect the athlete's self-confidence, namely; (1) technical swimming (2) Physical Conditions, and (3) Psychological. Broadly speaking, the level of self-confidence of athletes is formed in their physical condition by having a good presentation and above 44%. While in technical swimming only 39% and in psychological 17%. It can be concluded that what affects self-confidence the most is the physical condition, which can be interpreted to mean that the better the physical condition of the athlete, the more it forms self-confidence of the athlete